HUMAN-COMPUTER INTERACTION (HCI) DESIGN FOR DIGITAL QUR’AN APPLICATIONS: A STUDY ON ENHANCING USER EXPERIENCE FOR RECITATION AND STUDY - Setia, Lutfiyah Dwi; Hussain, Sara; Scott, James (Journal of Moeslim Research Technik, 2025)
The increasing popularity of digital Qur'an applications highlights the need for improved human-computer interaction (HCI) design to enhance user experience, particularly for recitation and study. While these applications provide valuable tools for accessing and learning the Qur'an, users often encounter challenges related to usability, navigation, and engagement. Effective HCI design is crucial to ensure that digital platforms are intuitive, user-friendly, and promote an enriching experience for Qur'an recitation and study. This research aims to explore HCI design principles tailored to digital Qur'an applications, with a focus on enhancing accessibility, usability, and user engagement. The study utilizes a mixed-methods approach, including user surveys, expert interviews, and usability testing, to identify key issues in existing applications and propose design improvements. The findings reveal that users value features such as audio controls for recitation, easy navigation, and integration with tafsir (interpretation). Additionally, personalized study modes and accessibility features significantly enhance user engagement. The study concludes that applying HCI design principles to digital Qur'an applications can improve user experience by making recitation and study more accessible, efficient, and engaging. The research offers actionable insights for developers aiming to create more user-centric Qur'an applications.